2016
DOI: 10.3168/jds.2016-11446
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by environment interaction for activity-based estrus traits in relation to production level for Danish Holstein

Abstract: The objective of this study was to investigate whether genotype by environment interaction exists for female fertility traits and production of energy-corrected milk at 70d in milk (ECM70). Fertility traits considered were the activity-based estrus traits interval from calving to first high activity (CFHA), duration of high activity episode (DHA), as an indicator for first estrus duration, and strength of high activity episode (SHA), as an indicator for first estrus strength. The physical activity traits were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…A recent study found the genetic variances of production traits varied at different THI levels, and a quadratic curve was observed in the heritabilities of protein yield [8]. In Danish Holstein populations, heterogeneities of heritabilities of several fertility traits were observed across different production levels or grass ratio in feed [6,33]. Although heritabilities vary across EGs in different analyses, patterns of heritabilities with changes in the environment are predictable.…”
Section: Variance Components Estimated From Rnms and G × Ementioning
confidence: 97%
“…A recent study found the genetic variances of production traits varied at different THI levels, and a quadratic curve was observed in the heritabilities of protein yield [8]. In Danish Holstein populations, heterogeneities of heritabilities of several fertility traits were observed across different production levels or grass ratio in feed [6,33]. Although heritabilities vary across EGs in different analyses, patterns of heritabilities with changes in the environment are predictable.…”
Section: Variance Components Estimated From Rnms and G × Ementioning
confidence: 97%
“…A recent study found the genetic variances of production traits varied in different THI levels, and a quadratic curve was observed in the heritabilities of protein yield [8]. In Danish Holstein populations, heterogeneities of heritabilities of several fertility traits were observed across different production levels or grass ratio in feed [6,33] Based on the t-test for the variance of the slope, a statistically significant GE was observed for all traits in this study [5]. Moderate to strong negative correlations were detected between the intercept and slope for each trait.…”
Section: Variance Components Estimated From Rnms and G × Ementioning
confidence: 98%
“…G×E exists if the variance of the slope was significantly different from zero by using a one-tailed t-test with the significance level of 0.05 [6,33]. One possible consequence of G×E is the re-ranking of animals across different environments [5];…”
Section: Magnitude Of G×ementioning
confidence: 99%
“…According to Nesser, Van Wyk and Ducrocq (2014) , the bull selection is important because selected animals should be adapted to the environmental conditions according to the locations in which their progeny will be raised. Thus, several studies have been carried out worldwide to identify the presence of GEI in Holstein herds to improve milking period ( Ismael et al., 2016a ), milk production ( Tiezzi, Los Campos, Parker Gaddis & Maltecca, 2017 ; Tsuruta, Lourenco, Misztal & Lawlort, 2015 ), fat and protein percentages, and somatic cell counts ( Streit, Reinhardt, Thaller & Bennewitz, 2013 ; Tiezzi et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%